Treatment Outcomes of HIV Infected Children After Initiation of Antiretroviral Therapy in Southwest China: An Observational Cohort Study - Zeng, Xiaoliang; Chen, Huanhuan; Zhu, Qiuying; Shen, Zhiyong; Lan, Guanghua; Liang, Jiangming; Liang, Fuxiong; Zhu, Jinhui; Xing, Hui; Shao, Yiming; Ruan, Yuhua; Zhang, Jianfeng; et al. (Frontiers in Pediatrics, 2022)
Abstract Background: The number of HIV infected children receiving antiviral treatment in Guangxi is increasing. Understanding factors and trends of mortality and attrition in HIV-infected children under antiretroviral therapy (ART) was an urgent need to improve treatment outcomes. This study aimed to estimate mortality and attrition rates and identify factors that were associated with mortality and attrition after ART initiation among children with HIV in Guangxi, China between 2004 and 2018. Methods: Cohort study data were extracted from the National Free Antiretroviral Treatment Program (NFATP) database, which has standard guidelines for core treatment indicators and other data at all HIV/AIDS treatment facilities in Guangxi. A total of 901 HIV-infected children who have started ART were included in the study. The study collected the following data: age, gender, WHO clinic stages before ART, CD4 cell count before ART, Cotrimoxazole prophylaxis (CTX) use before ART, initial ART regimen, malnutrition before ART, abnormal liver function before ART, abnormal kidney function before ART, severe anemia before ART, and the time lag between an HIV diagnosis and ART initiation. Results: HIV-infected children under ART had a mortality rate of 0.87 per 100 person-years (95% Confidence Interval (CI) 0.63-1.11), and an attrition rate of 3.02 per 100 person-years (95% CI 2.57-3.47). Mortality was lower among children with a CD4 count between 200-500 copies/ml (Adjusted Hazard Ratio (AHR) 0.22, 95% CI 0.09-0.55), and CD4 count ≥500 copies/ml (AHR 0.10, 95% CI 0.03-0.29); but higher among children with late ART initiation at 1-3 months (AHR 2.30, 95% CI 1.07-4.94), and at ≥ 3 months (AHR 2.22, 95% CI 1.04-4.74). Attrition was lower among children with a CD4 count ≥500 copies/ml (AHR 0.62, 95% CI 0.41-0.95), but higher among children with late ART initiation at 1-3 months (AHR 1.55, 95% CI 1.05-2.30). Conclusion: Supportive programs are needed to educate children’s families and parents on early ART, link HIV-infected children to care and retain them in care among other programs that treat and manage the medical conditions of HIV-infected children before ART initiation.